Regional Government Policy In Supporting The Minapolitan ProgramAs An Effort To Develop Fishery Cultivation In The Coastal Area OfThe Tapanuli Tengah Regency North Sumatra Province - Husnul Yaqin Harahap; Zulkarnain Zulkarnain; Darwis Darwis (Berkala Perikanan Terubuk, 2021)
This research was conducted on September 7-29, 2020 in Tapanuli Tengah Regency NorthSumatra Province. The purpose of this study was to determine the current minapolitanconditions in the coastal area of Tapanuli Tengah Regency North Sumatra Province,analyzing the development of the Minapolitan program that has been implemented as aneffort to develop aquaculture business in the coastal area of Tapanuli Tengah Regency, andthe next objective to analyze local government policies in supporting the Minapolitanprogram as an effort to develop fisheries cultivation in the coastal areas of TapanuliTengah Regency. The research method used by the author is a survey method. The results of the study was explained that the Minapolitan condition continues to run andis one of the priority programs of the local government in advancing the marine andfisheries sector in Tapanuli Tengah Regency until now. The development of theMinapolitan program that has been implemented has been effective since 2014 and is stillongoing today. And the result of the third research is that there are three sectors ofaquaculture that participate as a form of direct support from the Regional Government inthe success of the Minapolitan program in the coastal area of Tapanuli Tengah Regency.Among other things the first is the development of freshwater fish cultivation, secondly thedevelopment of brackish water aquaculture business, and third namely the development ofseawater aquaculture business.